NDM-1 carbapenemase resistance gene vehicles emergent on distinct plasmid backbones from the IncL/M family. (5th January 2022) - Lopez-Diaz, Maria; Ellaby, Nicholas; Turton, Jane; Woodford, Neil; Tomas, Maria; Ellington, Matthew J
Abstract: Objectives: To assess the genetic contexts surrounding bla NDM-1 genes carried on IncM plasmids harboured by six carbapenemase-producing Enterobacterales (CPE) isolates referred to the UK Health Security Agency's Antimicrobial Resistance and Healthcare Associated Infections (AMRHAI) Reference Unit. Methods: Between 2014 and 2018, the AMRHAI Reference Unit undertook WGS of CPE isolates using Illumina NGS. Nanopore sequencing was used for selected isolates and publicly available plasmid references were downloaded. Analysis of inc RNA, which encodes the antisense RNA regulating plasmidic repA gene expression, was performed and bioinformatics tools were used to analyse whole plasmid sequences. Results: Of 894 NDM-positive isolates of Enterobacterales, 44 NDM-1-positive isolates of five different species ( Citrobacter spp., Enterobacter cloacae, Escherichia coli, Klebsiella pneumoniae and Klebsiella oxytoca ) encoded the IncRNA locus of IncM2 plasmids. Long-read sequencing of six diverse isolates revealed related IncM2, NDM-1-encoding plasmids. Plasmid 'backbone' areas were conserved and contrasted with highly variable resistance regions. Sub-groupings of IncM2 plasmids encoding bla NDM-1 were detected; one sub-group occurred in five different health regions of England in every year. The diversity of NDM-1-encoding resistance gene integrons and transposons and their insertions sites in the plasmids indicated that NDM-1 has been acquired repeatedly by IncM2 variants. Conclusions: The use of sequencing helped inform: (i) a wide geographical distribution of isolates encoding NDM-1 on emergent IncM2 plasmids; (ii) variant plasmids have acquired NDM-1 separately; and (iii) dynamic arrangements and evolution of the resistance elements in this plasmid group. The geographical and temporal distribution of IncM2 plasmids that encode NDM-1 highlights them as a public health threat that requires ongoing monitoring.